Analysis Of Tool Performance During Ball-End Milling Of Aluminium Alloy 6061-T6 - Kasim, Mohd Shahir; Atan, Mohamad Hazizan; Che Haron, Che Hassan; A Ghani, Jaharah; Sulaiman, Mohd Amri; Mohamad, Effendi; Mohamad, Minhat; Abu Bakar, Mohd Hadzley; Saedon, Juri (Trans Tech Publications Inc., 2015)
This article presents the tool wear mechanism when machining Aluminium alloy 6061-T6 with PVD coated carbide under dry cutting condition. Cutting parameters selected were cutting speed, Vc = 115-145 m/min; feed rate fz = 0.15-0.2 mm/tooth and depth of cut, ap = 0.5-0.75 mm. The result showed the tool life of PVD TiAlN ranged from 11 to 97 min. Full factorial approach was employed to exhibit relationship between parameter input and output. From the analysis, cutting speed is the most significant factor to tool performance followed by feed rate and depth of cut. Another conclusion is that the most of failure modes occurred were notch wear and flaking near those found near depth of cut line.